Penguatan Sekolah Sehat Melalui Edukasi Gizi, Kesehatan Mental, dan Kebersihan Lingkungan Bagi Siswa Sekolah Dasar - Erwin Eka Saputra; Kasmawati Kasmawati; I Gede Panca; Arna Juwairiyah; Rifal Rifal; Fela Fela; Fitriani Fitriani; Sudirman Bira (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2026)
Elementary schools are strategic environments for developing healthy lifestyles in early childhood. However, various health issues persist in schools, such as a low understanding of balanced nutrition, a lack of awareness of mental health, and suboptimal environmental hygiene practices. This community service activity aims to strengthen the implementation of the healthy school concept through education on nutrition, mental health, and environmental hygiene for students at Konda 13 Public Elementary School. Implementation methods include interactive educational activities, counseling, discussions, simulations, and hands-on practice tailored to the characteristics of elementary school students. Educational materials include an introduction to balanced nutrition, the importance of maintaining mental health through simple emotional management, and the instilling of clean and healthy lifestyle habits in the school environment. The activity was carried out with the involvement of students, teachers, and the school administration as primary partners. Results showed an increase in student knowledge and awareness regarding healthy eating patterns, the importance of maintaining mental health, and environmental hygiene practices such as disposing of trash properly and maintaining classroom cleanliness. Furthermore, students demonstrated a more positive and participatory attitude during the activity. This program contributes to supporting the creation of a healthy, comfortable, and conducive school environment for the learning process. Thus, strengthening healthy schools through integrated education can be an effective strategy for improving the health and well-being of elementary school students.